(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure adequate preparation of business education graduates for self employment necessitated this study. The study was to determine the entrepreneurial competencies needed by business education graduates for entrepreneurial success in Anambra state. The study considered 237 business education graduates working in Anambra State. Tworesearchquestions guided the study and two hypotheseswere tested at 0.05 level of significance. Survey research design was adopted for the study. Data were collected using a 47 item questionnaire validated by three experts from the Faculty of Education, Nnamdi Azikiwe University, Awka. The test re-test reliability method and the Pearson Product Moment Coefficient were used to obtain the overall reliability coefficient of 0.85. The data collected using the questionnaire were analysed using mean values to answer the research questions while the null hypotheses were tested at 0.05 level of significance using z-test and ANOVA. The findings revealed that business education graduates need conceptual, organizing, strategic and human relation competencies for entrepreneurial success. It also revealed that respondents’ gender, qualifications and working experience did not affect their mean ratings on conceptual, strategic and human relation competencies but type of institution significantly affected their mean ratings on organizing competencies. It was recommended among others that tertiary institutions should encourage business education lecturers and students to organize workshops and conferences with a view to keeping them abreast of contemporary issues and needs ofthe business world and world of work.